2022
DOI: 10.1371/journal.pone.0274578
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and outcomes in light chain amyloidosis: An institutional registry of amyloidosis report in Argentina

Abstract: Light chain (AL) amyloidosis is a form of systemic amyloidosis, causing organ dysfunction, mainly affecting the heart and kidney. Patient-tailored and risk-adapted decision making is critical in AL amyloidosis management. There is limited real-world evidence data from Argentina and Latin America regarding the treatment approaches for AL amyloidosis. This retrospective cohort study aimed to describe the treatment patterns and outcomes in adult patients (>18 years) diagnosed with AL amyloidosis at the Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The network has published articles, won awards at conferences, taught courses and/ or seminars in Latin American countries, presented work at congresses and symposia, developed clinical practice guidelines on the diagnosis and treatment of amyloidosis in our region and published related articles on different aspects of amyloidosis, including documentation of the existence and magnitude of the disease, [34][35][36] the characteristics of the disease, [37][38][39] the understanding of the patterns of diagnosis and treatment, 40,41 and the development of strategies that seek to resolve or mitigate these problems and/or monitor their evolution. [42][43][44][45][46][47] The To address current gaps in knowledge, innovation and development are being conducted on diagnostic methods to identify the amyloid protein with local resources.…”
Section: Registries Bridge Gaps and Integratementioning
confidence: 99%
“…The network has published articles, won awards at conferences, taught courses and/ or seminars in Latin American countries, presented work at congresses and symposia, developed clinical practice guidelines on the diagnosis and treatment of amyloidosis in our region and published related articles on different aspects of amyloidosis, including documentation of the existence and magnitude of the disease, [34][35][36] the characteristics of the disease, [37][38][39] the understanding of the patterns of diagnosis and treatment, 40,41 and the development of strategies that seek to resolve or mitigate these problems and/or monitor their evolution. [42][43][44][45][46][47] The To address current gaps in knowledge, innovation and development are being conducted on diagnostic methods to identify the amyloid protein with local resources.…”
Section: Registries Bridge Gaps and Integratementioning
confidence: 99%
“…Moreover, it was suggested that the majority of patients present the λ type of monoclonal light chain [22,23]. Literature data have indicated that except for kidneys, the heart is the most frequently affected organ by light chain amyloidosis [24]. In addition, in patients with primary systemic immunoglobulin light chain amyloidosis, the association between cardiac biomarkers, echocardiographic parameters and FLCs was investigated.…”
Section: Monoclonal Gammopathymentioning
confidence: 99%